1968
DOI: 10.1002/rds196837766
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Main Geomagnetic Field in Locating Conjugate Points

Abstract: A sample distribution of conjugate points is calculated from various models of the main geomagnetic field, evaluated at different epochs. A summary of the conclusions is: (1) For L < 4 the errors are of the order of a few tens of kilometers; (2) older models of the field such as the Finch‐Leaton give results within a few degrees of the latest more accurate models; (3) use of the eccentric dipole approximation gives errors that range from a few tens of kilometers at high latitude to several hundred kilometers n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1969
1969
1976
1976

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Langel and Svalgaard [1974] showed that local ionospheric effects are important in consideration of polar cap geomagnetic changes. Figures 9 and 10 are an attempt to show seasonal and local time effects by comparison of the spectral characteristics at two pairs of conjugately located stations [Campbell and Matsushita, 1967;Cain, 1968]. The year 1967 was used in Figure 9 because the 1965 Great Whale River data were incomplete.…”
Section: Note That San Juan and Kakiokamentioning
confidence: 99%
“…Langel and Svalgaard [1974] showed that local ionospheric effects are important in consideration of polar cap geomagnetic changes. Figures 9 and 10 are an attempt to show seasonal and local time effects by comparison of the spectral characteristics at two pairs of conjugately located stations [Campbell and Matsushita, 1967;Cain, 1968]. The year 1967 was used in Figure 9 because the 1965 Great Whale River data were incomplete.…”
Section: Note That San Juan and Kakiokamentioning
confidence: 99%
“…The region was chosen to intersect: the Capetown anomaly, where a large difference in alti-REPORT 6345 rude occurs between conjugate and mirror points. A difference of about a degree is expected, owing to the difference in field models [Cain, 1968], mesh size, and methods of data contouring. Of more significance is a rather large difference in latitude, which is critically dependent on the mirror point altitude and the field line dip angle in the region between conjugate and mirror points.…”
mentioning
confidence: 99%